ANALISIS RISIKO K3 DALAM PELAKSANAAN REPARASI KAPAL "AHTS. KATALINA" MENGGUNAKAN METODE HAZARD IDENTIFICATION, RISK ASSESSMENT AND RISK CONTROL - Nadia Shalihah, (2023)
The shipbuilding industry is known for its high incidence of work-related accidents, necessitating the implementation of appropriate occupational health and safety (OHS) procedures and risk management protocols. Safety considerations within the shipbuilding sector are crucial due to the frequent exposure to hazardous working conditions, such as working at heights, in confined spaces, under high pressure, and on water surfaces. This study analyzes and evaluates work-related hazards and risks using a risk matrix during hull maintenance, repelating and construction, outfitting, and general work environments on the "AHTS. KATALINA" vessel at PT. XYZ. The research methodology employed is the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) approach, which utilizes qualitative and descriptive analysis techniques. This involves on-site observations, interviews with ship repair personnel, and the application of risk matrices to determine the level of risk associated with specific tasks. The findings of the study reveal a total of 94 potential risks, distributed across different risk levels: 11 classified as extreme, 23 as high, 41 as medium, and 19 as low. Consequently, recommended evaluation measures include the implementation of effective work instructions, ensuring comprehensive utilization of personal protective equipment (PPE), conducting regular and diligent work supervision, and providing routine OHS training to workers.